One-step hydrothermal synthesis of N-doped graphene/poly5-hydroxyindole composite materials for supercapacitor with ultra-long cycle stability and ultra-high energy storage performance. (November 2021) - Xu, Liming; Zhu, Danhua; Zhou, Weiqiang; Jiang, Fengxing; Wu, Yanli; Cai, Yue; Kang, Huan; Xu, Jingkun
Highlights: Ammonium persulfate acts as both the oxidant and N sources. 5-PHI nanospheres effectively inhibit the aggregation of GN. The as-prepared 5-PHI/GN = 1:1 has a high specific capacitance of 627.2 F g −1 at 2 A g −1 . The SC achieves an energy density of 35.5–30.0 Wh Kg −1 at the power density of 425–8500 W Kg −1 and excellent cycling stability. Abstract: Ultra-high energy storage N-doped graphene functionalized with nano-spherical poly(5-hydroxyindole) (5-PHI/GN) is prepared by a simple one-step hydrothermal method, in which ammonium persulfate as an oxidant initiates the in-situ polymerization of 5-hydroxyindole on the surface of graphene while acting as an N source to conduct N doping on graphene. By adjusting the ratio of 5-PHI to graphene, the 5-PHI/GN = 1:1 nanocomposite with the best synergistic effect is obtained. The electrochemical evaluation shows that the 5-PHI/GN=1:1 electrode has a maximum specific capacitance of 627.2 F g −1 at 2 A g −1 . In addition, a simple supercapacitor composed of two symmetrical 5-PHI/GN = 1:1 working electrodes, 5-PHI/GN = 1:1//5-PHI/GN = 1:1, was assembled, an energy density of 35.5 Wh kg −1 can be achieved under the power density of 425 W kg −1, and it has excellent long-term cycling stability (102.7% of initial specific capacitance was still maintained after 100, 000 cycles). These outstanding performances show that 5-PHI/GN = 1:1 is a promising candidate for supercapacitor electrode materials. Graphical abstract: Image, graphical abstract